Binary hypothesis-based impact damage detection for composite material system embedded with fiber Bragg gratings. (10th May 2017) - Yeager, Mike; Whitaker, Anthony; Whisler, Daniel A.; Kim, Hyonny; Gregory, William; Key, Chris; Todd, Michael
Abstract : In recent years, the use of composite materials has helped achieve ever-increasing performance requirements in marine, aerospace, and civil structures. A parallel interest in the structural health monitoring of composites has developed to further improve performance by reducing overall life-cycle costs. In this work, a network of embedded fiber Bragg gratings is employed as part of a damage detection system for an impact damage scenario in a composite laminate material system. Delamination damage is incrementally introduced into the laminate via repeated impacts with a drop weight pendulum system. Using vibration time histories between impacts from a simulated, pseudorandom operational loading, and damage-sensitive features were extracted and placed within a Mahalanobis distance-based discrimination framework. The statistical modeling for hypothesis testing is also presented to give a full, systems-level approach to a damage detection system from data acquisition to ultimate decision making.